"Together, We Make Football": The NFL's "feminine" discourses. (2nd January 2016) - Johnson, Victoria E.
ABSTRACT: This article presents an analysis of the National Football League's (NFL's) contemporary address to female fans through gendered appeals. These are designed to build and strengthen affective bonds between women and the league and mitigate acute public criticism regarding the sport's current concussion, domestic violence, and other brand crises. The essay uses Stuart Hall's conceptualization of critical conjuncture with humanistic television studies methods of formal/textual analysis to contextualize advertisements for the NFL's charitable initiatives, its "NFL for Her" merchandise promotions, and its advertising campaigns with Verizon Wireless. Beyond the NFL, analyzing the league's appeals to female fans allows consideration of how female athleticism and athletic fandom have increasingly become critical sites to visualize neoliberal logic.